A legal study on internet service provider: rights and liabilities for defamation via the internet / Nik Nurul Aishah Nik Rashid, Isma Nadia Ajis and Nor Adila Razak - Nik Rashid, Nik Nurul Aishah; Ajis, Isma Nadia; Razak, Nor Adila (Faculty of Law, 2011)
Defamation on the internet is not a new issue anywhere in the world. Rightfully, a person being defamed will take action against the defamer. However, the broadness of internet makes it hard to identify the real identity of the defamer which hard for the victim to bring an action against the defamer. The Internet Service Providers (ISPs) are sued instead. In Malaysia, defamation is governed by Defamation Act 1957. However this act is in comprehensive in dealing with the ISPs' rights and liabilities when compared to the laws of other countries. This project analyses the rights and liabilities of the ISPs in Malaysia specifically in defamation via the internet.